2020
DOI: 10.1111/bcp.14335
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and (hydroxy)chloroquine–azithromycin combination: Should we take the risk for our patients?

Abstract: The coronavirus disease 2019 pandemic has caught the scientific community and hospitals off-guard, and the race is on as clinicians grapple with novel treatment strategies and constantly changing recommendations. Patients with mental health disorders are particularly vulnerable to the coronavirus outbreak for various reasons, including cognitive impairment, little awareness of risk, diminished efforts regarding personal protection and more barriers in accessing timely health services. 1Only few therapeutic op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 5 publications
0
23
0
2
Order By: Relevance
“…The most frequent potential adverse event was cardiac toxicity (increased risk of QT prolongation), which alone accounted for almost 90% of the predicted DDIs during hospitalisation. This is not unexpected because the cardiovascular safety of the drugs currently used to treat SARS-CoV-2 infection is still a subject of debate in the scientific community [ 13 – 15 , 27 30 ]. Some of the concern is due to the observation that patients with COVID-19 are at increased risk of developing cardiovascular diseases regardless of treatment because the reported decrease in potassium levels can cause electrocardiographic changes such as a prolonged QT interval [ 27 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequent potential adverse event was cardiac toxicity (increased risk of QT prolongation), which alone accounted for almost 90% of the predicted DDIs during hospitalisation. This is not unexpected because the cardiovascular safety of the drugs currently used to treat SARS-CoV-2 infection is still a subject of debate in the scientific community [ 13 – 15 , 27 30 ]. Some of the concern is due to the observation that patients with COVID-19 are at increased risk of developing cardiovascular diseases regardless of treatment because the reported decrease in potassium levels can cause electrocardiographic changes such as a prolonged QT interval [ 27 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Half of the patients with COVID-19 enrolled in the study were aged > 65 years, the threshold for assessing PIMs and the ACB established by consensus guidelines [ 15 17 ]. Using the updated Beers criteria, we found that the large majority of our patients had at least one PIM, with no difference between admission and hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Caution must also be exercised when considering its use for pregnant women with underlying mental health problems as HCQ may interact with antipsychotics, anti-depressants and methadone increasing the risk of QTc-prolongation, torsade de pointes (TdP) and potentially death. 51…”
Section: Chloroquine and Hydroxychloroquinementioning
confidence: 99%
“…The cessation of smoking, inherent to hospitalization, can also cause unexpected drug interactions. Only the drugs for which a proven risk of interaction exists will be presented below [66].…”
Section: Drugs Used In Neuropsychiatric Diseasesmentioning
confidence: 99%